Theory Underpinning of 2013 English Curriculum as Revealed in Syllabus and English Textbook in Vocational High School - Nur Kamalinda, Mega (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
This study aims to find out the basic theories exist in the English curriculum as revealed at syllabus and English textbook. The researcher used documents such as the syllabus and English textbooks for class X at one of Vocational High School in Garut. The research method used by the researcher is qualitative research and document analysis as a research design. Data collection was done by analyzing documents in the form of the 2013 curriculum, such as the English syllabus and English textbooks for class X. The results show that there are 2 theory underpinning as revealed in English syllabus and English Textbook including the theory of teaching included Genre Based Approach and theory of learning included behaviorism, cognitive constructivism and social constructivism.